Elevated circulating fibrocyte levels in hemodialysis‐dependent end‐stage renal disease patients. Issue 4 (16th June 2021) - Li, Xinjian; Liu, Xing; Zhang, Haipeng; Zhang, Ruining; Li, Guangping
Abstract: Introduction: Numerous studies have demonstrated that end‐stage renal disease (ESRD) patients undergoing hemodialysis (HD) have high myocardial fibrosis (MF) levels. Circulating fibrocytes are bone marrow‐derived circulating mesenchymal progenitors, and new evidence suggests a vital role for fibrocytes in the development of MF. This study aimed to investigate whether fibrocyte levels are elevated in patients undergoing HD and its influence factors. Methods: We carried out a flow cytometry analysis to measure the proportion of peripheral blood circulating fibrocytes in a cohort of 126 healthy control individuals and 161 subjects with HD. Cardiac function and morphology were assessed by electrocardiogram and transthoracic echocardiogram. Findings: Compared to healthy controls, individuals with ESRD had significantly higher levels of circulating fibrocytes. There was a strong correlation between the frequency of fragmented QRS (fQRS) and circulating fibrocytes in HD patients. Furthermore, higher fibrocytes correlated to increasing age, dialysis age, left ventricular mass index (LVMI), left ventricular ejection fraction (LVEF), and hypertension complication. On multivariate analysis, the dialysis age [odds ratio (OR) 1.011, 95% confidence interval (CI) 1.003–1.019, p = 0.006], LVMI (OR 1.012, 95% CI 1.002–1.022, p = 0.016), hypertension (OR 4.303, 95% CI 1.129–16.406, p = 0.033), and fQRS (OR 2.439, 95% CI 1.049–5.262, p = 0.038) were significant independent predictors of fibrocytes percentage. Discussion: We concluded that bone marrow‐derived circulating fibrocytes were significantly increased in ESRD patients with HD compared with controls. Our data suggested that these cells might play essential roles during MF in HD patients.